Influence Mechanism of Employee Playfulness Personality on Employee Creative Deviance - Liu, Qiang; Zhao, Zhongwei; Liu, Yiran; Guo, Yu; He, Yao; Wang, Hao (Frontiers in Psychology, 2022)
Based on the questionnaire survey data of employees in high-tech enterprises, we introduce mediating variables of positive impression management motivation and harmonious innovation passion, integrate moderating variables of employee growth need strength and professional mission sense, and empirically discuss the influence mechanism of employee playfulness personality on employee creative deviance. The empirical analysis results show that employee playfulness personality has a significant positive influence on employee creative deviance, positive impression management motivation and harmonious innovation passion play partial mediating roles in the relationships between employee playfulness personality and employee creative deviance, employee growth need strength negatively moderates the relationships between positive impression management motivation and employee creative deviance, the more significant the employee growth need strength, the weaker the mediating effect of employees playfulness personality on employee creative deviance through positive impression management motivation, and there is a moderated mediating effect.